Developing IT-Based Mathematics Learning TAPPS Model to Improve High School Student’s Problem-Solving Skills - Rif'an, Muhamad Ghoni (Jurnal Pendidikan Matematika, 2023)
Mathematical problem-solving skill is a student skill in order to be able to use mathematical activities to answer questions in mathematics, problems in other sciences and problems in everyday life. Three-dimensional space as a part closely related to everyday life cannot be separated. The objective is to develop IT-Based TAPPS model learning tool to  improve student’s three-dimensional geometric subject  problem-solving skill using IT-Based TAPPS Model. The research method is research and development using Thiagarajan paradigm to define, design and develop steps. Three representative classes from MAN 01 Kudus are the samples for the research. The research of learning, motivation, abilities, procedures, teacher and pupil reaction, and problem-solving skill are the variables. The data are collected using validation sheets, tests, questionnaires, observation, and problem solving soft-skill test sheet (all in succession). The research is genuine showing the average scores based on syllabus, lesson plans, student books, student worksheets, and problem solving soft-skill test in the range of 1– 5.  The values are 4.5, 4.44, 3.8, 4.38, and 4.38. The learning process is practical learning process. It is signed by the positive responses from both students and teachers. The effect of the students' skills and motivation on problem-solving efficiency is 60.5%. The average score of the test's result for problem-solving skill is 83.78. It is more than the passing grade of 70. The result shows that in average, IT-Based TAPPS Model is more effective to solve problems than ekspository approache. The research is judged to be reliable, efficient and applicable.Kemampuan pemecahan masalah matematis adalah suatu keterampilan pada diri peserta didik agar mampu menggunakan kegiatan matematik untuk memecahkan masalah dalam matematika, masalah dalam ilmu lain dan masalah dalam kehidupan sehari-hari dan ruang dimensi tiga merupakan bagian yang erat kaitannya dengan kehidupan sehari-hari. Penelitian bertujuan mengembangkan perangkat pembelajaran Model TAPPS berbasis IT untuk meningkatkan kemampuan pemecahan masalah pada materi dimensi tiga. Penelitian ini merupakan penelitian pengembangan dengan menggunakan model Thiagarajan, yang terdiri atas tahap pendefinisian, tahap perancangan, dan tahap pengembangan. Penelitian dilakukan di MAN 01 Kudus pada tiga kelas sampel penelitian. Variabel penelitian meliputi perangkat pembelajaran, motivasi, keterampilan proses, respon guru dan siswa, dan kemampuan pemecahan masalah. Teknik pengumpulan data (berturut-turut) menggunakan lembar validasi, tes, angket, observasi, dan lembar TKPM. Hasil penelitian menunjukan rataan nilai silabus, RPP, buku siswa, LKS, dan TKPM berturut-turut dalam rentang 1-5 adalah 4,5; 4,44; 3,8; 4,38 dan 4,38 sehingga perangkat pembelajaran tergolong valid. Respon positif ditunjukkan oleh siswa dan guru terhadap pembelajaran, yang mengindikasikan perangkat pembelajaran praktis. Kemampuan pemecahan masalah meningkat. Motivasi dan keterampilan proses siswa berpengaruh sebesar 60,1% terhadap kemampuan pemecahan masalah siswa. Rataan hasil tes kemampuan pemecahan masalah 83,78 melebihi batas KKM 70, sehingga rataan kemampuan pemecahan masalah yang belajar menggunakan TAPPS berbasis IT lebih baik dari rata-rata kemampuan pemecahan masalah yang menggunakan metode ekspository. Dapat disimpulkan bahwa perangkat pembelajaran valid, praktis, dan efektif dan dapat diterapkan.